The Politicization Conversation: A Call to Better Define and Measure the Concept. Issue 1 (3rd January 2022) - Limbocker, Scott; Richardson, Mark D.; Selin, Jennifer L.
Abstract: Across disciplines and contexts, scholars vary in their conception of politicization. This variation reveals a need for more consistent concept definition and measurement of the extent to which politics influence administration. We engage this need by providing a typology of politicization that includes consideration of the actions of elected officials, political appointees, and merit‐based administrators. We then assess dynamic differences across the typology in the United States using personnel records spanning four decades, measures of insulation derived from statutory language, and three surveys of senior federal executives. Our analysis provides a research agenda for scholars who seek to examine the politicization of the executive branch .